2(x+2)=-2x+36

Simple and best practice solution for 2(x+2)=-2x+36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+2)=-2x+36 equation:


Simplifying
2(x + 2) = -2x + 36

Reorder the terms:
2(2 + x) = -2x + 36
(2 * 2 + x * 2) = -2x + 36
(4 + 2x) = -2x + 36

Reorder the terms:
4 + 2x = 36 + -2x

Solving
4 + 2x = 36 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
4 + 2x + 2x = 36 + -2x + 2x

Combine like terms: 2x + 2x = 4x
4 + 4x = 36 + -2x + 2x

Combine like terms: -2x + 2x = 0
4 + 4x = 36 + 0
4 + 4x = 36

Add '-4' to each side of the equation.
4 + -4 + 4x = 36 + -4

Combine like terms: 4 + -4 = 0
0 + 4x = 36 + -4
4x = 36 + -4

Combine like terms: 36 + -4 = 32
4x = 32

Divide each side by '4'.
x = 8

Simplifying
x = 8

See similar equations:

| -47=3(5x+2)-8 | | x^3+y^3+8y-8x=0 | | 5-3g+6(2g-7)= | | x^2-x+y^2+2y=0 | | 2(x-2)+2(x+5)=2x+2(2x-1) | | 4=1/2x | | (5x-4)^n/n^3 | | 0.5x*10= | | 25=0.03/x | | cos^5(20)=c*cos^5(20)+cos^3(20)+cos(20) | | 3+m=6+3 | | 1x(1x(230/5)) | | cos^5(20)=x*cos^5(20)+cos^3(20)+cos(20) | | z^4-256=0 | | cos^5(20)=a*cos^5(20)+b*cos^3(20)+c*cos(20) | | 2x-7=-3x-9 | | cos^5(x)=0 | | -37=4x-5 | | 0.216=0.20/(1-x) | | -2sen(2x-10)-1=0 | | 870-(5x+8y+20)=105 | | 5x+8y=745 | | 56-2x=12 | | 0.22=0.20/(1-x) | | 0.2/(1-x)=0.22 | | 0.22=0.2/(1-x) | | $9.75/24=5.85/n | | X+0.5x=38 | | 1.2x=x-60000 | | 7/10-2/5n | | 10x+16y=1538 | | 3x+2+2x-8=8x-9-5x+6 |

Equations solver categories